Sweden's self-perceived global role: Promises and contradictions. (December 2019) - Simons, Greg; Manoilo, Andrey
Abstract: Sweden has a global brand as being a democratic, happy and progressive society that is in consensus. However, when looking more closely at the key brand and reputational components of the Swedish international brand and reputation it is possible to see the various irregularities and contradictions that are present.